Ciri-ciri Usahawan Berjaya dari Perspektif Al-Qur'an - Wan Hussin, Wan Sabri (Jurnal Usuluddin, 2003)
This article is about findings of a study which was done to identify some characteristics of entrepreneurs as stated in the Qur'an. These characteristics are being compared with the opinion of the western scholars, attempts is made to develop a preliminary model of successful entrepreneurs. Sources of information are reading literature especially the translated version of Qur'an and other materials on entrepreneurs and businessmen. Findings of the study show some universal traits of successful entrepreneurs as being discussed by the western scholars. Anyhow the objective of being an entrepreneur from the perspective of Islam is different from what being taught by the western scholars. Profit in terms of ringgit is not the ultimate aim, but having blessing from Allah the Almighty is something expected most. Measurement of success is based on happiness forever, before and after death.